Commissioning of the multiparametric geophysical observatory at Shoal Bay, South Andaman and the preliminary results. (15th January 2021) - Mahavarkar, Prasanna; Bhadra, Debkumar; John, Jacob; Dongre, Varun; Iype, Anil; Mukherjee, Shyamoli; Veenadhari, B.; Vijaykumar, K.; Sharma, Nitin; Birthare, Pradeep Kumar
Highlights: Indian Institute of Geomagnetism is operating MPGO at Port Blair in South Andaman. Signatures of December 26, 2004 mega earthquake on mainland India were recorded. In house developed Proton Precession Magnetometer was installed at the MPGO. Attempt to co-relate the earthquake precursor signatures by ICM is made. Long period MPGO data was analyzed and found to be as per the observatory standard. Abstract: The Indian Institute of Geomagnetism (IIG) is operating Multiparametric Geophysical Observatory (MPGO) at Port Blair in South Andaman. We report here on the commissioning of MPGO and the quality of data collected by this observatory. The base line values are regularly computed with the aid of the declination inclination magnetometer, in house developed proton precession magnetometer and the flux gate magnetometer. The total field computed by the vector magnetometer is all time compared with direct measurements from the scalar magnetometer. An attempt to co-relate the precursor seismo-electromagnetic emissions of the earthquake event by the induction coil magnetometer is made. The seismic station of the observatory is capable of recording seismic events within the vicinity of ≈200 km. Further MPGO is upgrading and some more experiments are planned for the future.